Causal associations between gut microbiota and adverse pregnancy outcomes: A two-sample Mendelian randomization study - Li, Chuang; Liu, Caixia; Li, Na (Frontiers in Microbiology, 2022)
Growing evidence indicates that gut microbiota may be closely associated with a variety of adverse pregnancy outcomes (APOs), but a causal link between gut microbiome and APOs has yet to be established. We comprehensively investigated the relationship between gut microbiota and APOs causa to identify specific causal bacteria that may be associated with the development and occurrence of APOs by conducting a two-sample Mendelian randomization (MR) analysis. The microbiome genome-wide association study (GWAS) from the MiBioGen consortium was used as exposure data, and the GWAS for six common APOs was used for outcome data. The single nucleotide polymorphisms (SNPs) that significantly correlated to exposure, from published available GWAS, were selected as instrumental variables (IVs). We used the inverse variance weighted (IVW) test as the main MR analysis to estimate the causal relationship. Mendelian randomization pleiotropy residual sum and outlier (MR-PRESSO) and MR-Egger regression were used to confirm the presence of horizontal pleiotropy and to exclude outlier SNPs. We performed Cochran’s Q test to assess the heterogeneity among SNPs associated with each bacterium. The leave-one-out sensitivity analysis was used to evaluate whether the overall estimates were affected by a single SNP. Our analysis shows a causal association between specific gut microbiota and APOs. Our findings offer novel insights into the gut microbiota–mediated development mechanism of APOs.